1996
DOI: 10.1016/s0006-3495(96)79445-6
|View full text |Cite
|
Sign up to set email alerts
|

Chloride-dependent sarcoplasmic reticulum Ca2+ release correlates with increased Ca2+ activation of ryanodine receptors

Abstract: The mechanism by which chloride increases sarcoplasmic reticulum (SR) Ca2+ permeability was investigated. In the presence of 3 microM Ca2+, Ca2+ release from 45Ca(2+)-loaded SR vesicles prepared from procine skeletal muscle was increased approximately 4-fold when the media contained 150 mM chloride versus 150 mM propionate, whereas in the presence of 30 nM Ca2+, Ca2+ release was similar in the chloride- and the propionate-containing media. Ca(2+)-activated [3H]ryanodine binding to skeletal muscle SR was also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
23
0

Year Published

1997
1997
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 30 publications
10
23
0
Order By: Relevance
“…The ability of myoplasmic Cl -to potentiate Ca 2+ leakage from the SR was Ca 2+ dependent, as it was not observed when the [Ca 2+ ] was strongly buffered to a very low level (10 nM or pCa 8) (Table 1). This Ca 2+ dependent increase in Ca 2+ efflux is very similar to the effect reported by Fruen et al [10], where 150 mM Cl -increased the rate of Ca 2+ release from porcine SR vesicles in the presence of 3 µM Ca 2+ , but had little if any effect at 30 nM Ca 2+ . In the experiments here at pCa 6.7 (i.e.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The ability of myoplasmic Cl -to potentiate Ca 2+ leakage from the SR was Ca 2+ dependent, as it was not observed when the [Ca 2+ ] was strongly buffered to a very low level (10 nM or pCa 8) (Table 1). This Ca 2+ dependent increase in Ca 2+ efflux is very similar to the effect reported by Fruen et al [10], where 150 mM Cl -increased the rate of Ca 2+ release from porcine SR vesicles in the presence of 3 µM Ca 2+ , but had little if any effect at 30 nM Ca 2+ . In the experiments here at pCa 6.7 (i.e.…”
Section: Discussionsupporting
confidence: 90%
“…However, more recent experiments have provided evidence that high myoplasmic [Cl -] directly enhances the activation of RyR-1 [10,24], supporting an earlier proposal of Hasselbach and Migala [12] that this is the mechanism by which Cl -induces Ca 2+ release (see also [5]). Interestingly, the effect was not present in the cardiac SR vesicles [10] and cardiac fibres do not show Cl --induced Ca 2+ release [7]. Furthermore, experiments with permeabilized skeletal muscle fibres from mutant newborn mice lacking RyR-1 showed that, under conditions where there should be little or no osmotic effects (K + -methanesulphonate replaced with choline chloride), Cl --induced Ca 2+ release was largely or completely absent [14], strongly indicating that such release is predominantly mediated by RyR-1.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Thus the absolute magnitude of the increase in ryanodine binding (i.e., [ 3 H]ryanodine binding at a given perchlorate concentration over that in the absence of perchlorate) was not significantly different for normal and MHS SR vesicles [3.05 ± 0.31 pmol/mg and 2.52 ± 0.42 pmol/mg for normal and MHS SR respectively at 40 mM perchlorate (P > 0.05)]. Finally, as reported by Fruen et al [4,5], there was no indication of a maximum stimulation of ryanodine binding by perchlorate over the range of perchlorate concentrations examined in this study (Fig. 4, inset).…”
Section: Potentiation Of Twitch Tension By Perchloratesupporting
confidence: 68%
“…Previous work from our laboratory has suggested that, whereas RYR1 channels exhibit changeable Ca 2ϩ activation properties, cardiac RYR2 channels appear to exhibit a more consistent Ca 2ϩ -activable state (43). In terms of the present model (Fig.…”
Section: Dantrolene May Act Directly At Ryr1 Channels To Limit Activamentioning
confidence: 54%